Differential Subordination Results for Holomorphic Functions Related to Differential Operator - Kareem Wanas, Abbas; Swamy, S R (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2019)
,In the present work, we introduce and study a certain class of holomorphic functions defined by differential operator in the open unit disk . Also, we derive some important geometric properties for this class such as integral representation, inclusion relationship and argument estimate.